EXPOSURES AND RISK FACTORS OF CORONA VIRUS AMONG HEALTH CARE WORKERS AND NEED FOR PREVENTIVE MEASURES IN COMBINED MILITARY HOSPITAL RAWALPINDI - Siddiqi, Fuad Ahmad; Mehreen, Sobia; Ahmed, Adeel; Bashir, Tariq; Ahmad, Javed; Hassan, Fayyaz; Mahmood, Fatima (Pakistan Armed Forces Medical Journal, 2021)
Objective: Prospective To determine the various risk factors and exposures for spread of Corona Virus Disease 2019 (COVID19) among health care workers working at Combined Military Hospital Rawalpindi. Study Design: Cross sectional study. Place and Duration of Study: Combined Military Hospital, Rawalpindi, from Apr to Jul 2020. Methodology: A total of 134 health care workers who were infected with COVID-19, were included in study. A structured questionnaire was attained after informed consent and approval from hospital ethical committee. Data was analyzed using SPSS-19 statistical software. Results: Overall, 134 of 2591 Health care workers (Health care workers) in Combined Military Hospital Rawalpindi tested positive for COVID-19 during the study period. The infection rate was 5.17%. Among them 25 (18.7%) were women and 109 (81.3%) were men. There was not statistical difference in infection rate between male and female health care workers p=0.156). The infection rate in clinical category was significantly higher than non-clinical category (p<0.001. The infection rate in nursing assistants was significantly higher than the doctors (p=0.021). Personal protective equipment was optimally provided to health care workers except for goggles and face shields whose provision and use were both lacking. Conclusion: Health care workers are at high risk of developing COVID-19. There is need for extensive training, easy availability of personal protective equipment and strict compliance to infection control policies.